2013
DOI: 10.1682/jrrd.2012.04.0074
|View full text |Cite
|
Sign up to set email alerts
|

Role of sensory and motor intensity of electrical stimulation on fibroblastic growth factor-2 expression, inflammation, vascularization, and mechanical strength of full-thickness wounds

Abstract: Abstract-Electrical stimulation (ES) profoundly affects angiogenesis by modulating the production of angiogenic factors. We evaluated the effect of sensory (direct current, 600 microamperes) and motor (monophasic pulse current, 2.5 to 3 milliamperes, 300-microsecond pulse duration, 100 Hz) intensities of cathodal current on the release of fibroblastic growth factor-2 (FGF-2) at the wound site and also the biomechanical and histological properties of healed skin. Ninety-six male, SpragueDawley rats were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
0
24
0
5
Order By: Relevance
“…Several investigations have reported that ES can enhance angiogenesis by the upregulation of angiogenic factors, such as VEGF and FGF-2 [14,16,33]. Morris et al reported that ES (square wave pulsed direct current, 11 mA amplitude, 40 ms interpulse interval, 5 or 110 µs pulse duration) induced a significant increase in VEGF level in ischemic wounds in the ears of rabbits [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations have reported that ES can enhance angiogenesis by the upregulation of angiogenic factors, such as VEGF and FGF-2 [14,16,33]. Morris et al reported that ES (square wave pulsed direct current, 11 mA amplitude, 40 ms interpulse interval, 5 or 110 µs pulse duration) induced a significant increase in VEGF level in ischemic wounds in the ears of rabbits [15].…”
Section: Discussionmentioning
confidence: 99%
“…Morris et al reported that ES (square wave pulsed direct current, 11 mA amplitude, 40 ms interpulse interval, 5 or 110 µs pulse duration) induced a significant increase in VEGF level in ischemic wounds in the ears of rabbits [15]. Asadi et al reported that applying cathodal direct current at sensory intensity induces significant enhancement of VEGF [14] and FGF-2 [33] levels in incisional wounds. In a clinical study, Bevilacqua et al investigated the effect of frequency-modulated ES and TENS on the release of VEGF in diabetic and nondiabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The ES modality is less of a factor with regards to angiogenesis compared to wound closure and tensile strength with only a benefit of DC noted over AC . Sensory threshold current intensity appears more beneficial compared to higher current intensities and cathode is superior to anode stimulation with respect to neo‐vascularization…”
Section: Discussionmentioning
confidence: 99%
“…With ES augmenting all stages of wound healing, it may provide the necessary key to optimizing wound healing in animals. It may help to avoid fibroproliferative disorders such as EGT by downregulating inflammation through inhibition of cytokine release, improvement of tissue oxygenation and coordination of angiogenesis . However, there are concerns that ES could be detrimental and drive granulation tissue formation and exacerbate such conditions by stimulating an over‐exuberant angiogenic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation